KEKUASAAN DAN SOLIDARITAS PADA KALIMAT PERCAKAPAN SEHARI-HARI DALAM KEHIDUPAN MASYARAKAT - Kitra Asoka Pradestania; Wiwik Yulianti (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
This research is that the social relations between the speaker and the interlocutor are reflected in power and solidarity. A speaker uses language not only to express but to create a representation of himself in relation to others with whom he interacts. The purpose of this study is to explain the forms of power and solidarity that occur in everyday life. This research is a qualitative descriptive study. This study uses a sociolinguistic approach. This study explains the phenomena that occur in people's lives. This research uses the method of observing. The basic techniques used are observation techniques and note-taking techniques. The results of this study are to find out the various forms of power and solidarity from conversational sentences that occur in people's lives. Keywords: Power, Solidarity, Sociolinguistics